Basic Life Support and Cardiopulmonary Resuscitation Training for Pharmacy Students and the Community by a Pharmacy Student Committee - Goddard, Kara B. (American Journal of Pharmaceutical Education, 2010)
OBJECTIVE: To create a self-sufficient, innovative method for providing cardiopulmonary resuscitation (CPR) education within a college of pharmacy using a student-driven committee, and disseminating CPR education into the community through a service learning experience. DESIGN: A CPR committee comprised of doctor of pharmacy (PharmD) students at the University of Tennessee College of Pharmacy provided CPR certification to all pharmacy students. The committee developed a service learning project by providing CPR training courses in the community. Participants in the course were required to complete an evaluation form at the conclusion of each training course. ASSESSMENT: The CPR committee successfully certified more than 1,950 PharmD students and 240 community members from 1996 to 2009. Evaluations completed by participants were favorable, with 99% of all respondents (n = 351) rating the training course as either “excellent” or “good” in each of the categories evaluated. CONCLUSION: A PharmD student-directed committee successfully provided CPR training to other students and community members as a service learning experience.